Model of Circular Economy in Environmental Management. Case Study - SALNIKOVA, Anastasia; KOVALEV, Andrey; IOSIFOV, Valery; ALMASTYAN, Nairuhi (Journal of Environmental Management and Tourism, 2021)
The transition to circular economy models is a big challenge for enterprises, since it forces them not only to change established supply chains, pay extra attention to the quality and durability of manufactured products, develop schemes for the collection and subsequent disposal of products that have worked out their life, but also actively develop eco-innovation activities and participate in R&D more actively. The aim of this work is to study examples of the implementation of circular business models from the leading EU-based companies. The focus of the research on European companies is due to the fact that the European Union has been implementing a plan for the transition to a circular economy since 2015. In order to track the nature of applied eco-innovation in the field of CE the case-studies from the leading EU-based companies have been analysed. The choice of the companies is determined by their commitment to the CE principles and availability of the obtained results in their annual reports. The case-studies have shown all reviewed companies demonstrated beyond average commitment to the principles of CE in all aspects (sayings, doings and materiality). Their strong adherence is determined by their intense environmental impact and leading positions at regional and global markets.